The Influence of Nurse Manager's Transformational Leadership Style on Nurse's Medication Safety Dimediation Performance in Intention Room of Private Hospital in Pekanbaru - Andika Eka Putra; Siti Dyah Handayani; Nuryakin Nuryakin (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2023)
The purpose of this study was to analyze the effect of the nurse manager's transformational leadership style on performance and medication safety.Respondents in this study aremedical staff working in a private hospital Pekanbaru.The samples used were 96 respondents with quantitative methods using SEM and Smart PLS, with a sampling techniqueconveniencesampling. Hypothesis testing using SEM-Partial Least Square; test the validity and reliability using confirmatory factors, cronbach's alpha and composite reliability. The results of this study indicate that the transformational leadership style of nurse managers has a positive and significant effect on performance and medication safety, performance has a positive and significant effect on medication safety and mediation performance has a positive and significant effect on nurse manager transformational leadership style on medication safety.